(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
It is known that the phosphorites of the Central Kyzyl Kum are poor raw materials and have a high calcium modulus. The peculiar structural features characterizing the high reactivity of highcarbonate Kyzylkum phosphorites give reason to believe that the most optimal solution is to process them into effective fertilizers by chemical activation of phosphate raw materials.